Combination of S-adenosylmethionine and mouthguard for oral self-mutilation in Lesch-Nyhan syndrome. Issue 4 (July 2021) - Narai, Takashi; Harada, Yusei; Fujii, Nobuyuki; Tamura, Takayuki; Doi, Rieko; Kodani, Isamu
Abstract: Lesch-Nyhan syndrome (LNS) is characterized by frequent oral self-mutilation (OSM). Although various treatments have been suggested, our limited knowledge regarding the exact pathogenic mechanism of self-mutilation in LNS makes it difficult to manage self-injurious behavior and there is a need for novel treatments. Herein, we describe the case of a 11-year-old boy with LNS and OSM who was conservatively treated using S-adenosylmethionine (SAM) and a mouthguard. This resulted in significant improvement in OSM, and the patient remains stable at 16 years old. This case demonstrates that combination treatment with SAM and a mouthguard should be considered for the management of OSM in LNS, as it can maintain the functionality and health of the oral cavity and improve a patient's quality of life.